Examiners’ Perspectives on Assessment Criteria for Doctoral Dissertations and Oral Examinations in English Language Education in Thailand - Adunyarittigun, Dumrong; Byram , Michael; Sriharuksa, Kamonrat; Vathanalaoha , Kriangkrai; Phornprapha, Jiraporn (Journal of Studies in the English Language, 2026)
While concerns regarding evaluation criteria in doctoral assessment persist, existing research has largely focused on student experiences. Apart from a single-institution account (Adunyarittigun et al., 2023), the practices of dissertation assessment and oral examination in Thailand’s English language education (ELE) programs remain largely uninvestigated. This study explores doctoral assessment practices in ELE and related fields in Thailand from the perspectives of experienced examiners, with particular attention to evaluation criteria. Of the 121 eligible participants, 71, each with experience supervising and/or examining doctoral dissertations, completed a survey; 19 informants agreed to participate in a follow-up interview. Descriptive statistics were used to summarize participants’ backgrounds and perceptions, while qualitative data were analyzed using thematic analysis with intercoder reliability checks. The findings revealed that, although institutional documents outline assessment procedures, they lack detailed rubrics. Interviews identified seven key evaluation criteria: mastery of the intellectual landscape, argumentative rigor, effective presentation, research integrity, methodological rigor, originality, and publishability. The examiners adopted a holistic approach, emphasizing the interconnectedness of these criteria. Nevertheless, argumentative rigor was expected to be evident throughout the dissertation, suggesting greater emphasis on this criterion than reported in other international contexts. Examiners also showed tolerance for minor linguistic inaccuracies, prioritizing argument quality, and demonstrated a distinct, context-specific interpretation of originality in terms of utility. The findings provide insights into discipline-specific criteria for doctoral assessment. Informing candidates of these expectations may help demystify the assessment process and support them more effectively during their doctoral journey.